2021
DOI: 10.1186/s12983-021-00400-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial alternative oxidase contributes to successful tardigrade anhydrobiosis

Abstract: Anhydrobiosis can be described as an adaptation to lack of water that enables some organisms, including tardigrades, to survive extreme conditions, even some that do not exist on Earth. The cellular mechanisms underlying anhydrobiosis are still not completely explained including the putative contribution of mitochondrial proteins. Since mitochondrial alternative oxidase (AOX), described as a drought response element in plants, was recently proposed for various invertebrates including tardigrades, we investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Moreover, H . exemplaris might provide valuable data concerning AOX involvement in efficient protection against stress factors affecting mitochondria [ 39 ]. This also applies to aging as the mean lifespan under laboratory conditions of about two months makes the species suitable for studies of AOX activity role in aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, H . exemplaris might provide valuable data concerning AOX involvement in efficient protection against stress factors affecting mitochondria [ 39 ]. This also applies to aging as the mean lifespan under laboratory conditions of about two months makes the species suitable for studies of AOX activity role in aging.…”
Section: Discussionmentioning
confidence: 99%
“…As we have recently shown for the tardigrade M . inceptum , BHAM can be described as an efficient inhibitor of tardigrade AOX [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the cells are described as the main form of energy storage, enabling a proper nutrient regime for different tissues as well as providing protection to tissues by producing protective metabolites [19,55,56]. Moreover, it has been shown that energetic support is also important during the tun stage [57]. Therefore, we assumed that tuns that were to survive should have had the correct ultrastructure of these cells, enabling their proper function also during/after rehydration.…”
Section: Typical Tun Appearance Does Not Rule Out Degeneration Of Sto...mentioning
confidence: 99%
“…These studies primarily focused on testing the survival of tardigrades in environmental extremes, including radiation, changes in humidity, and high temperatures, or repeated anhydrobiosis at different life stages. The studies included research on DNA repair mechanisms and stress proteins synthesis on the basis of genomic analyses [ 21 , 25 , 27 , 29 , 33 35 , 37 41 , 45 , 46 , 48 , 51 , 55 , 59 , 60 ]. The conclusion from these studies shows that different tardigrade species have a high degree (80–90%) of survival after short periods of anhydrobiosis.…”
Section: Introductionmentioning
confidence: 99%
“…exemplaris , a very high survival rate (~ 90%) was reported for Mil . inceptum after 30 and 60 days in anhydrobiosis [ 41 ].…”
Section: Introductionmentioning
confidence: 99%